PENGARUH PENERAPAN TEKNIK QUICK ON THE DRAW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 13 SIJUNJUNG - Mardelyni, Agustini; Delsi K, Delsi K; Cesaria, Anna (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was based on the students who were not interested in math and the students whose understanding of mathematical concept was low. This research is aimed at knowing the students understanding of mathematical concept with the apply of the technique of quick on the draw is better than the students understanding of mathematical concept with the apply of conventional learning. The kind of the research was the experimental research with the random device to the subject class VIII.2 was chosen as experimental class and class VIII.3 as control class. The instrument used was the test understanding of mathematical concept in the form of essay in reliability 0.971. Based on the data analysis result, it was known that two sample classes were distributed normally, homogeny and tcount = 1.74 and ttable = 1.675 because tcountÂ > ttable with Â = 0,05 those, the hypothesis was accepted. Therefore, it was concluded that the studentsâ understanding of mathematical concept with the apply of quick on the draw technique is better than the students understanding of Â mathematical concept with the apply of conventional learning in class VIII SMPN 13 of Sijunjung.